Circulating CD4+, CD8+, and double-negative T cells in ischemic stroke and stroke-associated infection: a prospective case-control study - Telec, Magdalena; Frydrychowicz, Magdalena; Kazmierski, Radosław; Wojtasz, Izabela; Dworacki, Grzegorz; Kozubski, Wojciech; Łukasik, Maria (Frontiers in Cellular Neuroscience, 2025)
IntroductionAdaptive immunity after a stroke results in a shift of T cells between compartments, leading to peripheral lymphopenia and an increased number of T cells within the brain lesion. Stroke-associated infection (SAI) presents a clinically significant challenge in stroke units. The role of T-cell subsets in the post-stroke immune response and in SAI remains unclear. Thus, we aimed to observe the quantitative changes of circulating CD4+, CD8+, double-negative T cells, and the CD4+/CD8+ ratio in stroke and SAI.MethodsWe prospectively assessed circulating CD4+, CD8+, and double-negative T cells using flow cytometry in 52 patients on days 1, 3, 10, and 90 after ischemic stroke. We compared the results to those obtained from age-, sex-, and vascular risk factor-matched controls. We analyzed lymphocyte parameters in relation to clinical outcome, SAI, infarct lesion volume, and risk factor burden.ResultsThere were no differences in the studied parameters between stroke patients and controls, as well as between subjects with and without SAI. A higher percentage of CD4+ T cells and a higher CD4+/CD8+ ratio correlated with better clinical status in the acute and subacute phases, while CD8+ T cells showed the opposite correlation. The percentage of CD8+ T cells positively correlated with CRP levels during the acute and subacute phases of stroke, as well as in the control group. A negative correlation was noted between the percentage of CD4+ T cells on D1 and the serum CRP level on D10 after stroke. Similarly, the CD4+/CD8+ ratio on D1 negatively correlated with CRP on D1, D3, and D10. In patients with a history of hypertension (HT), there was a higher percentage of CD8+ T cells and a lower percentage of CD4+ T cells in the acute phase of stroke than those without HT.